The Impact of the Quizizz Application on Students' Self-Efficacy - Yani Yani; Ratna Mei Vidya; Dhruvayoti Tiirtheshvara; Gede Rasben Dantes; Gede Indrawan (Jurnal Penelitian Pendidikan IPA, 2024)
The integration of technology into education can facilitate more effective learning, promote collaborative learning among students, and substantially increase self-efficacy. This study aims to analyze the Quizizz application's impact on students' test preparation self-efficacy. Quizizz, a gamified assessment tool, offers game elements such as points, leaderboards, and direct feedback, which are expected to improve student motivation and self-confidence. Data collection involved 215 students from Purwoharjo High School uses a mixed-method approach, including interviews, documentation, and questionnaires. The results show that most students positively perceive Quizizz as a tool that enhances their academic self-efficacy. Gamification elements such as leaderboards and immediate feedback significantly boost motivation, allowing students to focus on areas of improvement and manage their learning time more effectively. However, some variations in the impact on self-efficacy were observed, especially among students with lower self-confidence. This research concludes that Quizizz can effectively enhance students’ self-efficacy when adequately integrated into the learning process